樺太の記憶伝承プロジェクトが及ぼした大学生の態度変容に関する考察 - 牧野,竜二; マキノ,リュウジ; MAKINO,Ryuji (中央大学政策文化総合研究所, 2023)
application/pdf The island of Sakhalin, which can be seen from the shore of Wakkanai City, was Japanese territory “Karafuto” until the end of World War II. After the war, Karafuto residents became repatriates and migrated to various parts of Japan. Wakkanai City has a history of economic development as the population increased due to the immigration of Karafuto repatriates. However, Wakkanaiʼs young people are not interested in Karafuto. Therefore, this paper examines the attitude changes of university students in Wakkanai City who participated in “The Project of Handing Down the Memories of Karafuto” (The Karafuto Project), which collects the testimonies of Karafuto repatriates for a documentary film. First, it observed changes in the remarks and actions of university students who participated in the projectʼs early work. Next, it referred to previous research and determined that there was a notable attitude change. Then, as a hypothesis, it set up a model of the attitude change process of the students. Furthermore, to verify the model, it conducted a survey of the students who participated in the 2020 and 2021 projects. As a result, this study had two findings. The first is that many of the students who participated in the Karafuto Project changed their attitudes, as hypothesized. There was an orderly connection of changes in each layer of cognition, affect, and behavior. The second is that the content and extent of the studentsʼ attitude changes differed depending on the student. It is inferred that the difference in the time and density of the learning task has an effect. This project has the potential to become a new and effective method of peace learning. departmental bulletin paper